Pendampingan UMKM Peternak Ayam Petelur Dunia Unggas Melalui Penerapan Manajemen Mutu Terpadu Total Quality Management (TQM) - Farika Nursasi; Karina Kemala; Sudarmiatin Sudarmiatin; Yuli Soesetio (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2026)
This community service activity aims to improve the quality of business management at the "Dunia Unggas" egg-laying chicken farming MSME in Malang Regency through the implementation of Total Quality Management (TQM). The main problems faced by partners include an unstructured quality management system, low levels of cage cleanliness, the absence of systematic production records, and suboptimal feed management and disease control. The implementation method uses a participatory approach with stages of diagnostics, intervention planning, program implementation, and monitoring and evaluation. The intervention program focused on the preparation of Standard Operating Procedures (SOPs), improving sanitation and biosecurity, developing a production recording system, optimizing feed management, and increasing disease control capacity. The results of the activity showed improvements in aspects of operational regularity, cage cleanliness, consistency of production records, and partners' understanding of more professional business management. In addition, there was an increase in the quality and stability of egg production. Thus, the implementation of TQM through mentoring has proven effective in increasing operational efficiency and competitiveness of MSMEs in a sustainable manner.